Propane selective adsorbent

Beta-type zeolite with specific properties addresses the inefficiencies of existing materials by enhancing propane adsorption and selectivity, facilitating cost-effective and efficient propane recovery and propylene purification.

JP2025016373APending Publication Date: 2025-01-31TOSOH CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024114703
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-21
Filing Date
2024-07-18
Publication Date
2025-01-31

AI Technical Summary

Technical Problem

Existing propane adsorption materials, such as Zif-8 and STT Zeolite, are expensive, have low heat resistance, and inefficient in adsorbing propane from propane-propylene mixed gas, making industrial application costly and time-consuming.

Method used

Utilizing beta-type zeolite with a silica molar ratio of 1000 or more and a specific NMR spectrum, containing less than 200 mass PPM of alkaline metal oxide, which enhances propane adsorption efficiency and selectivity.

Benefits of technology

The beta-type zeolite effectively adsorbs propane from propane-propylene mixed gas, enabling efficient industrial propane recovery and propylene purification, reducing costs and time requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016373000002
    Figure 2025016373000002
  • Figure 2025016373000001
    Figure 2025016373000001
Patent Text Reader

Abstract

To provide a propane adsorbent applicable as an industrial propane adsorbent while being capable of achieving an efficient selective adsorption of propane from a propane-propylene gas mixture, and also to provide at least one of a propane selective adsorption method using the same and a propylene purification method.SOLUTION: A propane selective adsorbent includes a beta type zeolite with a molar ratio of a silica 1000 or more to an alumina. In a spectrum measured by 29Si-DDMAS-NMR, the beta type zeolite has a fraction of 98% or more with regard to a total area of peaks each having a peak top within a range of chemical shift -120 to -108 ppm to a total area of peaks each having a peak top within a range of chemical shift -120 to -90 ppm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a propane selective adsorbent containing beta zeolite, a method for selectively adsorbing propane, and a method for purifying propylene. [Background technology]

[0002] Propylene is an important basic raw material in petrochemistry, and is industrially produced by refining a mixed gas containing propane and propylene (hereinafter also referred to as a "propane-propylene mixed gas"). As a method for purifying propylene with superior energy efficiency compared to conventional refining methods, a refining method in which propane in a propane-propylene mixed gas is adsorbed by a propane adsorbent and then rectified has been considered (for example, Non-Patent Document 1).

[0003] In such a purification method, a metal-organic framework, ZIF-8 (Non-Patent Document 2) or STT-type zeolite (Non-Patent Document 3) is used as a propane adsorbent. [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] Adsorption News, Japan Society of Adsorption, Vol.34, No.1 (Serial No.132) (2020) 13-19 [Non-Patent Document 2] Langmuir,29(2013)8592-8600 [Non-Patent Document 3] Microporous and Mesoporous Materials,236(2016)100-108 Summary of the Invention [Problem to be solved by the invention]

[0005] Metal-organic frameworks such as ZIF-8 used in Non-Patent Document 2 are expensive. In addition, ZIF-8 has low heat resistance and needs frequent replacement. Therefore, the purification method using a metal-organic framework as a propane adsorbent is very expensive and difficult to apply industrially.

[0006] On the other hand, the STT zeolite of Non-Patent Document 4 has a slow propane adsorption rate, and in particular, it takes a long time to adsorb propane from a propane-propylene mixed gas having a low propane content. Moreover, the selective removal efficiency of propane from a propane-propylene mixed gas containing a trace amount of propane is very low, making it difficult to purify the gas within a practical time.

[0007] In view of these circumstances, an object of the present disclosure is to provide at least one of a propane adsorbent that is applicable as an industrial propane adsorbent and that can be expected to efficiently selectively adsorb propane from a propane-propylene mixed gas, a method for selectively adsorbing propane using the same, and a method for purifying propylene. [Means for solving the problem]

[0008] In this disclosure, we have focused on zeolite, which is a cheaper material than metal organic frameworks, as an adsorbent capable of selectively adsorbing propane from a propane-propylene mixed gas containing propane. As a result, we have found that zeolite that has a specific composition and exhibits a specific NMR spectrum can function as a selective adsorbent for propane.

[0009] That is, the present invention is as described in the claims, and the gist of the present disclosure is as follows. [1] A beta zeolite having a molar ratio of silica to alumina of 1000 or more, the beta zeolite being 29A propane selective adsorbent in which the ratio of the total area of ​​peaks having their peak tops in the chemical shift range of -120 ppm or more and -108 ppm or less to the total area of ​​peaks having their peak tops in the chemical shift range of -120 ppm or more and -90 ppm or less in a spectrum measured by Si-DDMAS-NMR is 98% or more. [2] The propane selective adsorbent according to [1], wherein the beta zeolite has an alkali metal content, calculated as an oxide, of 200 mass ppm or less. [3] The propane selective adsorbent according to [1] or [2], wherein the beta zeolite has a ratio of the propane adsorption equilibrium constant K1 to the propylene adsorption equilibrium constant K2 of 2.00 or more. [4] The propane selective adsorbent according to any one of [1] to [3], wherein the beta zeolite contains fluorine. [5] A method for selectively adsorbing propane, comprising contacting the beta zeolite contained in the propane selective adsorbent described in any one of [1] to [4] with a mixed gas containing propane and propylene. [6] A method for purifying propylene, comprising contacting the beta zeolite contained in the propane selective adsorbent described in any one of [1] to [4] with a mixed gas containing propane and propylene. Effect of the Invention

[0010] The present disclosure can provide at least one of a propane adsorbent that is applicable as an industrial propane adsorbent and that can be expected to efficiently selectively adsorb propane from a propane-propylene mixed gas, a method for selectively adsorbing propane using the same, and a method for purifying propylene. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 shows NMR spectra of the adsorbents (zeolites) of Example 1 and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] First, the meaning of each term in this specification will be explained.

[0013] In this specification, "zeolite" refers to a compound having a regular structure in which skeleton atoms (hereinafter also referred to as "T atoms") are arranged via oxygen (O), and the T atoms are composed of at least one of metal atoms and metalloid atoms. Examples of metal atoms include at least one selected from the group consisting of aluminum (Al), titanium (Ti), iron (Fe), zinc (Zn), gallium (Ga) and tin (Sn), with aluminum being preferred. Examples of metalloid atoms include at least one selected from the group consisting of boron (B), silicon (Si), germanium (Ge), arsenic (As), antimony (Sb) and tellurium (Te), with silicon being preferred.

[0014] A "zeolite-like substance" is a compound having a regular structure in which T atoms are oxygen-mediated, and the T atoms contain at least an atom other than a metal or a metalloid. Examples of zeolite-like substances include complex phosphorus compounds containing phosphorus (P) as the T atom, such as aluminophosphate (AlPO) and silicoaluminophosphate (SAPO). "Zeolite-like substances" are distinguished from "zeolites" in which the T atoms are composed of at least one of metal atoms and metalloid atoms.

[0015] In this specification, the term "crystalline aluminosilicate" refers to a zeolite in which the T atoms are composed of aluminum (Al) and silicon (Si). The term "crystalline aluminosilicate" refers to a zeolite in which the T atoms are composed of aluminum (Al) and silicon (Si), and is distinguished from a zeolite in which the T atoms are composed substantially only of silicon (Si) (i.e., a crystalline silicate). In addition, the "crystalline aluminosilicate" shows a crystalline XRD peak in its powder X-ray diffraction (hereinafter also referred to as "XRD") pattern, and is distinguished from an "amorphous aluminosilicate" that does not show a crystalline XRD peak.

[0016] In this specification, the term "crystalline silicate" refers to a zeolite in which T atoms are substantially composed of silicon (Si). The term "T atoms are substantially composed of silicon (Si)" does not mean that the T atoms are composed of silicon (Si) only, but also means that the T atoms may contain metal atoms and / or metalloid atoms (e.g., aluminum) in the production raw materials (e.g., silica source) as inevitable impurities in addition to silicon (Si). More specifically, the term "crystalline silicate" refers to a zeolite in which T atoms are composed of silicon only, and a zeolite in which T atoms are composed of aluminum and silicon only, and the molar ratio of silica to alumina (hereinafter also referred to as "SiO2 / Al2O3 molar ratio") is 2000 or more. Note that the "crystalline silicate" is distinguished from the "amorphous silicate" in which the powder X-ray diffraction (hereinafter also referred to as "XRD") pattern shows a crystalline XRD peak, but does not show a crystalline XRD peak.

[0017] In this specification, the term "crystalline aluminoborosilicate" refers to a zeolite in which the T atoms are composed of aluminum (Al), silicon (Si), and boron (B). The term "crystalline aluminoborosilicate" refers to a zeolite in which the T atoms are composed of aluminum (Al), silicon (Si), and boron (B), and is distinguished from a zeolite in which the T atoms are essentially composed of silicon (Si) and boron (B) only (i.e., a crystalline borosilicate). In addition, the term "crystalline aluminoborosilicate" refers to a zeolite in which the T atoms are ...

[0018] In this specification, the term "crystalline borosilicate" refers to a zeolite in which T atoms are substantially composed of silicon (Si) and boron (B). The term "T atoms are substantially composed of silicon (Si) and boron (B)" does not mean that the T atoms are composed of silicon (Si) and boron (B), but allows the inclusion of metal atoms and / or semimetal atoms (e.g., aluminum) in the inevitable impurities that may be contained in the raw material for production (e.g., silica source) in addition to silicon (Si) and boron (B). More specifically, the term "crystalline borosilicate" in this specification refers to a zeolite in which T atoms are composed of silicon and boron, and a zeolite in which T atoms are composed of aluminum, silicon, and boron, and the molar ratio of silica to alumina (hereinafter also referred to as "SiO2 / Al2O3 molar ratio") is 2000 or more. In addition, "crystalline borosilicate" exhibits crystalline XRD peaks in its powder X-ray diffraction (hereinafter also referred to as "XRD") pattern, and is distinguished from "amorphous borosilicate" which does not exhibit crystalline XRD peaks.

[0019] In this specification, the "ordered structure" of zeolite refers to a skeletal structure specified by the skeleton code (hereinafter, simply referred to as the "skeleton code") established by the Structure Commission of the International Zeolite Association, and a skeletal structure having an intergrowth structure described on the website of the International Zeolite Association, http: / / www.iza-structure.org / databases / . For example, "MFI zeolite" is a zeolite having a skeleton structure specified by the skeleton code "MFI". Also, for example, "beta zeolite" is a zeolite belonging to the beta intergrowth family Beta, and is typically a zeolite having a skeleton structure (intergrowth structure) composed of intergrowths consisting of about 60% polymorph Beta_A and about 40% polymorph Beta_B, similar to the Reference Material "Zeolite Beta". Note that the intergrowth ratio of beta zeolite referred to in this application is the same as that of the above "Zeolite Beta" unless otherwise specified. Also, in the Reference Material, "Zeolite Beta" of the International Zeolite Society (DO Material) is described at "https: / / asia.iza-structure.org / IZA-SC / DO_structures / DO_material_rm.php?IFN=Beta" on the website of the International Zeolite Society. The framework structure or intergrowth structure of each zeolite can be identified, for example, by comparison with the XRD pattern (hereinafter also referred to as "reference pattern") described in Zeolite Framework Types on the website of the International Zeolite Society.

[0020] In this specification, the XRD patterns include those obtained by XRD measurement under the following conditions. Acceleration current / voltage: 40mA / 40kV Radiation source: CuKα radiation (λ=1.5405Å) Measurement mode: Continuous scan Scan condition: 40° / min Measurement range: 2θ=3° to 43° Divergence vertical limit slit: 10mm Divergence / entrance slit: 1° Receiving slit: open Detector: D / teX Ultra Ni filter used

[0021] The crystalline XRD peak is a peak that is detected by identifying the 2θ of the peak top in the analysis of the XRD pattern using a general analysis software (e.g., IGOR Pro 8, manufactured by WaveMetrics, or SmartLab StudioII, manufactured by Rigaku). Although not particularly limited, the half-width (full width at half maximum) of the XRD peak can be, for example, 2θ=0.50° or less.

[0022] In this specification, the term "layered silicate" refers to a crystalline substance formed by stacking silicic acid sheets in which silicon tetrahedra are connected two-dimensionally. The layered silicate has a different framework structure (crystal structure) from zeolite, and layered silicates having a specific framework structure (crystal structure) are given names. Examples of the names of layered silicates include IEZ-1, IEZ-2, and ZIF-8. The framework structure of the layered silicate can be identified by comparison with the XRD pattern described in, for example, non-patent literature (Chem. Commun., 2007, 5188-5190).

[0023] In this specification, the term "metal organic framework" refers to a porous material formed by coordinate bonds between metal ions and organic compounds, and has a framework structure (crystal structure) different from that of zeolite. An example of the metal organic framework is ZIF-8.

[0024] Hereinafter, one embodiment of the present disclosure will be described. In the present disclosure, the configurations and parameters disclosed herein include any combination, and the upper and lower limits of the values ​​disclosed herein include any combination.

[0025] The propane selective adsorbent of this embodiment contains beta zeolite.

[0026] The beta zeolite contained in the propane selective adsorbent of this embodiment (hereinafter also referred to as "beta zeolite according to this embodiment") has a SiO2 / Al2O3 molar ratio of 1000 or more. When the SiO2 / Al2O3 molar ratio is less than 1000, the amount of counter cations of Al contained is large, and the counter cations strongly interact with propylene, so that the adsorption characteristics are more selective for propylene than for propane, and propane cannot be efficiently selectively adsorbed from the propane-propylene mixed gas. The SiO2 / Al2O3 molar ratio may be 1000 or more, but from the viewpoint of more efficiently selectively adsorbing propane, it is preferably 1500 or more, 2000 or more, 3000 or more, 10000 or more, or 20000 or more, and 500000 or less, 300000 or less, or 200000 or less. The upper and lower limits of the SiO2 / Al2O3 molar ratio may be in any combination, and examples of the range include 1500 to 500,000, 2000 to 300,000, 3000 to 200,000, 10,000 to 200,000, or 20,000 to 200,000.

[0027] The beta zeolite according to this embodiment is not particularly limited with respect to the T atoms constituting its framework structure, so long as the SiO2 / Al2O3 molar ratio is 1000 or more. From the viewpoint of more efficient selective adsorption of propane, however, it is preferable that the T atoms be a crystalline aluminosilicate consisting of aluminum and silicon, a crystalline silicate consisting essentially of silicon only, a crystalline aluminoborosilicate consisting essentially of aluminum, silicon, and boron, or a crystalline borosilicate consisting essentially of silicon (Si) and boron (B), and it is more preferable that the zeolite be a crystalline silicate or a crystalline borosilicate.

[0028] When the beta zeolite according to the present embodiment contains boron (B) as the T atom, the molar ratio of silica to boron oxide B2O3 (hereinafter also referred to as "SiO2 / B2O3 molar ratio") is preferably 500 or less, 200 or less, or 150 or less, and 10 or more, 20 or more, or 30 or more, from the viewpoint of more efficiently selectively adsorbing propane. The combination of the upper and lower limits of the above-mentioned SiO2 / B2O3 molar ratio is preferably 10 or more and 500 or less, 20 or more and 200 or less, or 30 or more and 150 or less, from the viewpoint of more efficiently selectively adsorbing propane.

[0029] The beta zeolite according to this embodiment is 29 In the spectrum measured by Si-DDMAS (Dipolar Decoupling - Magic Angle Spinning)-NMR, each peak having a peak top in the chemical shift range of -120 ppm to -90 ppm (hereinafter referred to as "Peak Q All Each peak having a peak top in the chemical shift range of -120 ppm to -108 ppm (hereinafter referred to as "peak Q") is compared with the total area (hereinafter referred to as "area S"). 4 (0Al) ") (hereinafter referred to as "area S Q4(0Al) ") ratio (hereinafter, "Q 4 The Q of beta zeolite is 98% or more. 4 If the (0Al) ratio is less than 98%, the material will contain a large amount of components that strongly interact with propylene, such as counter cations derived from Al and OH at defect sites, making it impossible to efficiently selectively adsorb propane from a propane-propylene gas mixture.

[0030] In this embodiment, Q 4 The (0Al) ratio can be calculated by the following formula (1). Q 4 (0Al) ratio = area S Q4(0Al) / area S×100 ···(1) In the above formula (1), the area S Q4(0Al) is the peak Q 4(0Al) Total area [cm 2 ], and the area S is the peak Q All Total area [cm 2 ], and Q 4 (0Al) ratio is area S to area S Q4(0Al) It represents the ratio [%].

[0031] Where: 29 Si-DDMAS-NMR is known as a means for analyzing the local structure around silicon atoms in the zeolite framework structure (for example, Yoshio Ono and Takeaki Yashima, eds., "Science and Engineering of Zeolites," pp. 61-67 (published by Kodansha Publishing, 2000)). 29 The chemical shifts of the spectra measured by Si-DDMAS-NMR have the degeneracy factor Q of the silicon atom. i (i=0~4) is reflected, 29 The spectrum measured by Si-DDMAS-NMR can reveal the bonding state between silicon atoms and T atoms via oxygen. i In the formula, i represents the number of oxygen atoms bridging the T atom among the four oxygen atoms contained in the SiO4 tetrahedron. That is, the degeneracy Q i means that i oxygen atoms among the four oxygen atoms contained in the SiO4 tetrahedron are shared by adjacent T atoms. For example, the degeneracy Q 4 The bonding mode can be represented as Si(OT)4.

[0032] Degeneracy is Q 4 Among silicon atoms in the SiO4 tetrahedron, silicon in the SiO4 tetrahedron in which all four oxygen atoms are bonded to adjacent silicon atoms (hereinafter referred to as "silicon represented by Si(OSi)4") is 29 The peaks with their tops in the chemical shift range of -120 ppm to -108 ppm in the spectrum measured by Si-DDMAS-NMR (i.e., peak Q 4 (0Al)On the other hand, silicon in an SiO4 tetrahedron in which at least one of the four oxygen atoms in the SiO4 tetrahedron is bonded to a T atom other than silicon (e.g., aluminum), or silicon in an SiO4 tetrahedron in which at least one of the four oxygen atoms in the SiO4 tetrahedron is a hydroxyl group (-OH) without being bonded to a T atom, 29 It belongs to a peak having a top in the range of -108 ppm to -90 ppm in the spectrum measured by Si-DDMAS-NMR. 4 The (0Al) ratio can be considered an indicator of the proportion of silicon represented by Si(OSi)4 among the silicon that constitutes the zeolite framework structure.

[0033] Beta zeolite 29 The Si-DDMAS-NMR measurement can be carried out using a general solid-state nuclear magnetic resonance apparatus (for example, AVANCE III 600, manufactured by Bruker). 29 The measurement conditions for Si-DDMAS-NMR can be, for example, the following conditions. 1 H resonance frequency: 600MHz 29 Si resonance frequency: 119.2MHz Rotor speed: 10kHz Repeat time: 30.0 seconds Accumulation count: 2048 times

[0034] Peak Q All The total area S is 29 Peak Q from the spectrum measured by Si-DDMAS-NMR measurement All and the separated peak Q All The area (integral value) of the peak Q 4 (0Al) The area S is the total area of Q4(0Al) teeth, 29 Peak Q from the spectrum measured by Si-DDMAS-NMR measurement 4 (0Al) and the separated peak Q 4 (0Al)It can be calculated by adding up the areas (integral values) of

[0035] 29 Peaks from the spectrum measured by Si-DDMAS-NMR measurement (hereinafter also referred to as "measured spectrum") All or Peak Q 4 (0Al) In order to separate the peaks, a conventionally known peak separation method (peak fitting) can be used. For example, All or Peak Q 4 (0Al) The least squares method assuming a function representing the peaks can be used for the separation. Examples of the function representing the peaks include a Gaussian function, a Lorentz function, a mixed function of a Gaussian distribution and a Lorentz distribution (Gauss-Lorentz), and a Voigt function. Peak separation by the least squares method may be performed using standard NMR data processing software (software name: ALICE2, JEOL). In addition, the peaks may be separated so that the relative error of the spectrum obtained by recombining the peak separations (hereinafter also referred to as the "calculated spectrum") with respect to the measured spectrum is less than 5% for any point (ppm).

[0036] In addition, the area S Q4(0Al) is the peak Q 4 (0Al) The sum of the areas of each peak is called peak Q. 4 (0Al) If there is one peak, the area of ​​that peak is the area S Q4(0Al) Similarly, the area S is the peak Q All The sum of the areas of each peak is called peak Q. All When there is one peak, the area of ​​that one peak can be taken as the area S.

[0037] The beta zeolite according to this embodiment has a SiO2 / Al2O3 molar ratio of 1000 or more, and Q 4The (0Al) ratio is sufficient to be 98% or more, and other configurations are not particularly limited, but from the viewpoint of more efficiently selectively adsorbing propane, the content of alkali metals in oxide equivalent is preferably 500 mass ppm or less, more preferably 200 mass ppm or less. The lower limit of the content of alkali metals in oxide equivalent can be 0 mass ppm or more, for example. From the viewpoint of more efficiently selectively adsorbing propane, the range of the content of alkali metals in oxide equivalent is preferably 0 mass ppm or more and 500 mass ppm or less, more preferably 0 mass ppm or more and 200 mass ppm or less.

[0038] The content of the alkali metal (content of alkali metal in oxide equivalent) can be determined by dividing the mass of the alkali metal contained in the beta zeolite, calculated as an alkali metal oxide, by the mass of the beta zeolite. When the beta zeolite contains two or more types of alkali metal, the content of the alkali metal in oxide equivalent means the total amount of the contents of each alkali metal (content of alkali metal in oxide equivalent). In addition, the content of the alkali metal in oxide equivalent of 0 ppm by mass means that the beta zeolite does not contain any alkali metal.

[0039] The beta zeolite according to the present embodiment is preferably produced by a fluoride method as described later. Therefore, the beta zeolite according to the present embodiment may contain fluorine (F). The fluorine (F) may be supported outside the framework of the beta zeolite, for example, in at least one of pores and ion exchange sites.

[0040] The BET specific surface area of ​​the beta zeolite according to this embodiment is not particularly limited, but from the viewpoint of more efficient selective adsorption of propane, it is preferred that the BET specific surface area be 300 m 2 / g or more 3000m 2 / g or less, and 2 / g or more 2000m 2 / g or less is more preferable, and 2 / g or more 1000m 2 The BET specific surface area can be measured by a general nitrogen gas adsorption method, for example, by applying the BET method to the results of nitrogen gas adsorption at -196°C.

[0041] The pore volume of the beta zeolite according to this embodiment is not particularly limited, but from the viewpoint of more efficiently selectively adsorbing propane, it is preferably 0.15 cm 3 / g or more 0.50cm 3 / g or less, and 0.20 cm 3 / g or more 0.40cm 3 The pore volume can be measured by a general nitrogen gas adsorption method, for example, by applying the t-plot method to the results of nitrogen gas adsorption at -196°C.

[0042] The beta zeolite according to the present embodiment is not particularly limited, but from the viewpoint of more efficiently selectively adsorbing propane, the ratio of the adsorption equilibrium constant K1 of propane to the adsorption equilibrium constant K2 of propylene (hereinafter also referred to as "K1 / K2") is preferably 2.00 or more, and more preferably 2.50 or more. The higher the K1 / K2 of the beta zeolite, the more preferable it is, and examples thereof include 30 or less or 10 or less. From the viewpoint of more efficiently selectively adsorbing propane, the range of K1 / K2 of the beta zeolite according to the present embodiment is preferably 2.00 or more and 30 or less, and more preferably 2.50 or more and 10 or less.

[0043] The adsorption equilibrium constant K1 of propane is a constant obtained by performing an adsorption test of propane at 25°C, plotting the measurement results (adsorption amount q1 and pressure p1) on a graph with a vertical axis of 1 / q1 and a horizontal axis of 1 / p1 (Langmuir plot), and approximating the result with the Langmuir adsorption isotherm expressed by the following formula (2). The adsorption equilibrium constant K2 of propylene is an adsorption equilibrium constant obtained by performing an adsorption test of propylene at 25°C, plotting the measurement results (adsorption amount q2 and pressure p2) on a graph with a vertical axis of 1 / q2 and a horizontal axis of 1 / p2 (Langmuir plot), and approximating the result with the Langmuir adsorption isotherm expressed by the following formula (3). The least squares method can be used as an approximation method. The propane adsorption test and the propylene adsorption test for determining the adsorption equilibrium constant K1 and the adsorption equilibrium constant K2 can be performed using a general adsorption apparatus (apparatus name: BELSORP Max, manufactured by Microtrack Bell). The test gas may be 10% by volume or more and 100% by volume or less of propylene, etc. For the propane adsorption test or the propylene adsorption test, it is preferable to use pretreated beta zeolite, and the pretreatment may be a reduced pressure heat treatment (2 Pa or less) at 400°C for 12 hours.

[0044] 1 / q1=(1 / Q1)×(1 / K1)×(1 / p1)+(1 / Q1) ···(2) In the above formula (2), q1 represents the amount of propane adsorbed [mol / kg], Q1 represents the saturated amount of propane adsorbed [mol / kg], p1 represents the pressure [kPa], and K1 represents the adsorption equilibrium constant of propane [kPa -1 ].

[0045] 1 / q2=(1 / Q2)×(1 / K2)×(1 / p2)+(1 / Q2) ···(3) In the above formula (3), q2 represents the amount of adsorption of propylene [mol / kg], Q2 represents the saturated adsorption amount of propylene [mol / kg], p2 represents the pressure [kPa], and K2 represents the adsorption equilibrium constant of propylene [kPa -1 ].

[0046] The beta zeolite according to this embodiment is not particularly limited, but from the viewpoint of more efficient selective adsorption of propane, the effective adsorption amount of propane is preferably 40 [mL (STP) / g] or more, more preferably 42 [mL (STP) / g] or more, and even more preferably 50 [mL (STP) / g] or more. In this embodiment, the effective adsorption amount of propane can be the change in the propane adsorption amount from a pressure of 0.1 kPa to 10 kPa in the Langmuir adsorption isotherm (approximation line) used to calculate the adsorption equilibrium constant K1 of propane. The higher the effective adsorption amount of propane of the beta zeolite, the more preferable it is, and for example, 200 [mL (STP) / g] or less, or 100 [mL (STP) / g] or less can be mentioned. From the viewpoint of more efficient selective adsorption of propane, the effective adsorption amount of propane of the beta zeolite according to this embodiment is preferably from 40 [mL(STP) / g] to 200 [mL(STP) / g], more preferably from 42 [mL(STP) / g] to 200 [mL(STP) / g], and even more preferably from 50 [mL(STP) / g] to 100 [mL(STP) / g].

[0047] The propane selective adsorbent of the present embodiment may be composed of only the above-mentioned beta zeolite, but may also contain other substances other than beta zeolite. Examples of other substances other than beta zeolite include one or more selected from the group consisting of a binder, a molding aid, and water.

[0048] The binder may be an organic binder, an inorganic binder, or both of these binders. The organic binder may be at least one selected from the group consisting of polyethylene oxide, hydroxyethyl methylcellulose, starch, corn starch, molasses, lactose, gelatin, dextrin, gum arabic, alginic acid, acrylic acid, polyethylene glycol, and polyvinylpyrrolidone. The inorganic binder may be at least one selected from the group consisting of clay, silica, alumina, and zirconia. From the viewpoint of suppressing the amount of propylene adsorption, the binder is preferably at least one selected from the group consisting of starch, acrylic acid, silica, alumina, and zirconia, and more preferably silica.

[0049] The content of the binder in the propane selective adsorbent of this embodiment can be, for example, 5% by mass or more and 70% by mass or less relative to 100% by mass of the propane selective adsorbent.

[0050] Examples of the molding aid include water-soluble or water-insoluble celluloses such as carboxylmethylcellulose (hereinafter also referred to as "CMC"), hydroxycellulose, hydroxypropylmethylcellulose, hydroxypropylcellulose, ethylcellulose, and cellulose nanofiber; guar gum derivatives such as at least one of guar gum and hydroxypropylguar gum; polysaccharides such as at least one selected from the group consisting of xanthan gum, welan gum, and gellan gum, which belong to biogums; polyethyleneimine derivatives; polyvinylvinylidone (hereinafter also referred to as "PVP"); alcohols such as at least one selected from the group consisting of glycerin, polyvinyl alcohol, and ethylene glycol derivatives; cationic, anionic, or nonionic surfactants; aqueous urethane; polyacrylic acid derivatives, and the like, and these may be contained not only alone but also in combination of two or more. The CMC may be sodium type carboxymethylcellulose. A preferred molding aid is at least one of CMC and hydroxypropylcellulose.

[0051] The content of the molding aid in the propane selective adsorbent of this embodiment can be, for example, 0.1% by mass or more and 10% by mass or less relative to 100% by mass of the propane selective adsorbent.

[0052] The water content in the propane selective adsorbent of this embodiment can be, for example, 0.1 mass % or more and 40 mass % or less relative to 100 mass % of the propane selective adsorbent.

[0053] The propane selective adsorbent of this embodiment contains a binder in addition to the beta zeolite described above, which makes it easier to mold the propane selective adsorbent of this embodiment into a predetermined shape. In addition to the beta zeolite and binder described above, the propane selective adsorbent of this embodiment contains a molding aid and water, which improves moldability. The propane selective adsorbent in the form of a molded body can be produced, for example, by molding a mixture of the beta zeolite and binder (and molding aid and water as necessary) described above into a predetermined shape and firing it. The shape of the molded body is not particularly limited, but at least one selected from the group consisting of spherical, approximately spherical, elliptical, cylindrical, polyhedral, and amorphous can be exemplified.

[0054] From the viewpoint of more efficient selective adsorption of propane and reducing pressure loss when a mixed gas containing propane and propylene (propane-propylene mixed gas) is passed through, the size of the molded body is preferably 0.1 mm or more and 4.0 mm or less in median diameter, and more preferably 0.3 mm or more and 2.0 mm or less in median diameter. The median diameter is the particle size (d 50 )

[0055] Next, a method for producing beta zeolite according to this embodiment will be described.

[0056] The beta zeolite according to this embodiment has a SiO2 / Al2O3 molar ratio of 1000 or more and Q 4 As long as the (0Al) ratio is 98% or more, any manufacturing method may be used to produce it, but it is preferable to produce it by the fluoride method using a fluorine compound as a mineralizer. - The fluoride method uses hydroxide (hydroxide ion (OH )) as a mineralizer. - )) compared to the general production method using 4 Therefore, by using the fluoride method, the Q 4 It becomes easier to produce beta zeolite having an (0Al) ratio of 98% or more. Note that the mineralizer is a substance that promotes the crystallization of the raw material composition.

[0057] The method for producing beta zeolite according to the present embodiment using the fluoride method will be described below. Note that the method for producing beta zeolite according to the present embodiment is not limited to the fluoride method described below.

[0058] The method for producing beta zeolite according to this embodiment using the fluoride method includes a crystallization step of crystallizing a composition containing at least a silica source, a structure directing agent source, a fluorine source, and water (hereinafter also referred to as a "raw material composition").

[0059] The silica source contained in the raw material composition is a compound containing silicon (Si), and may be one or more selected from the group consisting of colloidal silica, fumed silica, amorphous silica, sodium silicate, tetraethyl orthosilicate (hereinafter also referred to as "TEOS"), aluminosilicate gel, and amorphous aluminosilicate. TEOS is preferred as the silica source because it contains a small amount of impurities.

[0060] The structure directing agent source contained in the raw material composition may be any substance directing beta zeolite, and is not particularly limited, but may be tetraethylammonium cation. The structure directing agent source may be in the form of a salt, and may be one or more salts selected from the group consisting of hydroxide, chloride, and bromide. More specific examples of the structure directing agent source include one or more salts selected from the group consisting of tetraethylammonium hydroxide, tetraethylammonium chloride, and tetraethylammonium bromide.

[0061] The fluorine source contained in the raw material composition is a compound containing fluorine (F), and examples thereof include one or more selected from the group consisting of hydrofluoric acid, ammonium fluoride, sodium fluoride, silicon fluoride, ammonium fluorosilicate, and sodium fluorosilicate.

[0062] Here, Q 4 To produce beta zeolite with a (0Al) ratio of 98% or more, hydroxide ions (OH - ) is preferably not substantially contained in the raw material composition. For this reason, when a hydroxide is used as each raw material contained in the raw material composition, it is preferable to use hydrofluoric acid as the fluorine source. By using hydrofluoric acid as the fluorine source, hydrogen ions (H + ) is generated from hydroxide by hydroxide ion (OH - ) in the raw material composition, and reacts with hydroxide ions (OH - The amount of hydroxide ions (OH - The term "substantially free of hydroxide ions (OH - ) is sufficiently small, and the hydroxide ion (OH - ) is hydrogen ion (H + ) when the pH at 25°C is between 6 and 9, the amount of hydroxide ions (OH -) is substantially not contained. More specifically, the raw material composition contains hydroxide ions (OH - ) is, for example, 0 μmol / L or more and 10 μmol / L or less.

[0063] The water contained in the raw material composition may be, for example, distilled water, deionized water, pure water, or two or more of these. When the raw materials other than water contained in the raw material composition contain water, such as hydrates, structural water, or solvents, the water contained in the raw materials other than water can be considered as the water contained in the raw material composition.

[0064] The raw material composition may be composed only of the silica source, the structure directing agent source, the fluorine source, and water described above, but may also contain other raw materials other than these. Examples of such other raw materials include an aluminum source, an alkali source, and a boron source.

[0065] The aluminum source is a compound containing aluminum (Al), and examples thereof include one or more selected from the group consisting of aluminum isopropoxide, aluminum sulfate, aluminum chloride, aluminum hydroxide, pseudoboehmite, alumina sol, and amorphous aluminosilicate. Note that substances containing aluminum (Al) and silicon (Si), such as amorphous aluminosilicate, can be used not only as an alumina source, but also as the above-mentioned silica source.

[0066] The alkali source is a compound containing an alkali metal element, and examples thereof include compounds containing one or more alkali metal elements selected from the group consisting of sodium, potassium, cesium, and rubidium. The alkali source may be in the form of one or more salts selected from the group consisting of hydroxides, carbonates, chlorides, bromides, iodides, and sulfates containing an alkali metal element. The raw material composition may contain an alkali source, but from the viewpoint that the propane selective adsorbent of the present embodiment can more efficiently selectively adsorb propane, it is preferable that the raw material composition does not substantially contain an alkali source. Note that the term "substantially does not contain an alkali metal" means that the alkali metal in the raw material composition is below the detection limit, and although it depends on the detection capability of the measuring device, the content of the alkali metal in the raw material composition can be 0 ppm or more and 500 ppm or less.

[0067] The boron source is a compound containing boron, and examples thereof include one or more selected from the group consisting of boric acid, boron oxide, and sodium borate. Note that boric acid converts hydrogen ions (H + ) in the raw material composition, - ) can be reduced. For this reason, when hydroxides are used as the raw materials contained in the raw material composition, it is preferable to use boric acid as the boron source. Since boric acid is less likely to contain metal ions that can become impurities and has high solubility in water, it is easier to prepare the composition of the raw material composition compared to other boron sources.

[0068] The composition of the raw material composition is such that the SiO2 / Al2O3 molar ratio is 1000 or more, and Q 4 As long as a beta zeolite having a (0Al) ratio of 98% or more can be produced, there is no particular limitation, but an example of the composition of the preferred raw material composition can be the following molar composition: Note that each ratio in the following composition is a molar ratio, Si represents silicon (mol), Al represents aluminum (mol), HO represents water (mol), M represents an alkali metal element (mol), F represents fluorine (mol), SDA represents an organic structure directing agent (mol), OH represents a hydroxide ion (mol), and B represents boron (mol). Al / Si ratio=0 or more, preferably 0.00001 or more, and Less than 0.002, preferably 0.0015 or less SDA / Si ratio=0 or more, preferably 0.1 or more, and 2.0 or less, preferably 1.5 or less M / Si ratio=0 or more, preferably 0.001 or more, and 1.0 or less, preferably 0.3 or less HO / Si ratio = 4 or more, preferably 6 or more, and 100 or less, preferably 50 or less F / Si ratio=0 or more, preferably 0.3 or more, and 3.0 or less, preferably 2.0 or less OH / Si ratio = 0 or more, preferably 0.001 or more, and 1.0 or less, preferably 0.3 or less B / Si ratio=0 or more, preferably 0.01 or more, and 0.10 or less, preferably 0.05 or less

[0069] The raw material composition can be obtained by mixing the above-mentioned silica source, structure directing agent source, fluorine source, water, and other raw materials contained as necessary. The raw materials contained in the raw material composition may be mixed while heating. The heating temperature during mixing is not particularly limited, but can be, for example, 20°C to 80°C. In addition, the raw materials contained in the raw material composition may be mixed by mixing all components at the same time, or by premixing only some of the raw materials in advance to obtain a premixture, and then mixing the obtained premixture with the remaining raw materials to obtain the raw material composition.

[0070] The crystallization treatment of the raw material composition is not particularly limited as long as it can crystallize the raw material composition to obtain beta zeolite. A preferred crystallization treatment method is a method of subjecting the raw material composition to hydrothermal treatment. The hydrothermal treatment may be performed by placing the raw material composition in a sealed pressure-resistant container and heating it. Examples of hydrothermal treatment conditions include the following conditions. Treatment temperature: 110°C or higher, 130°C or higher, or 150°C or higher, and 210℃ or less, 200℃ or less, or 190℃ or less Processing time: 8 hours or more, 10 hours or more, or 15 hours or more, and 500 hours or less or 300 hours or less Processing pressure: Natural pressure

[0071] The crystallization treatment of the raw material composition is preferably carried out after adding seed crystals to the raw material composition, since this makes it easier to produce beta zeolite. The seed crystals are zeolite that have the function of promoting the crystallization of beta zeolite, and for example, beta zeolite can be used. The SiO2 / Al2O3 molar ratio of the beta zeolite used as the seed crystals is such that the SiO2 / Al2O3 molar ratio of the produced beta zeolite is 1000 or more and Q 4 As long as the (0Al) ratio is 98% or more, it is not particularly limited, but is preferably 1500 to 500000, more preferably 2000 to 300000, even more preferably 3000 to 200000, particularly preferably 10000 to 200000, and most preferably 20000 to 200000. The amount of seed crystals added can be, for example, 0.0001 to 1 times by mass, or 0.001 to 0.1 times by mass, relative to the silica source contained in the raw material composition (not including seed crystals).

[0072] The method for producing beta zeolite according to this embodiment may include, in addition to the above-mentioned crystallization step, one or more steps selected from the group consisting of a washing step, a drying step, and an SDA removal step.

[0073] The washing step is a step of washing the beta zeolite obtained by crystallization. For example, in the washing step, the beta zeolite obtained by crystallization may be washed with pure water.

[0074] The drying step is a step of removing moisture from the beta zeolite obtained by crystallization or from the beta zeolite that has been subjected to a washing treatment. The conditions of the drying treatment are not particularly limited as long as moisture can be removed from the beta zeolite. The drying temperature can be exemplified as 50°C or higher and 200°C or lower. The drying time can be exemplified as 1 hour or higher and 30 hours or lower. The atmosphere during drying can be exemplified as air.

[0075] The SDA removal step is a step of removing SDA (organic structure directing agent) contained in beta zeolite obtained by crystallization, beta zeolite that has been washed, or beta zeolite that has been dried. Usually, beta zeolite crystallized using SDA contains SDA in its pores. By including the SDA removal step, it is possible to remove the SDA contained in the beta zeolite.

[0076] The SDA removal treatment can be carried out under any conditions as long as SDA is removed. Examples of the method for removing SDA include at least one selected from the group consisting of a liquid phase treatment using an acidic aqueous solution, an exchange treatment using a resin or the like, and a heat treatment (thermal decomposition). From the viewpoint of production efficiency, the SDA removal treatment is preferably a heat treatment (thermal decomposition). The conditions for the heat treatment (thermal decomposition) are not particularly limited as long as SDA is removed. The heat treatment temperature can be 500° C. or higher and 900° C. or lower. The heat treatment time can be 1 hour or higher and 10 hours or lower. The atmosphere during the heat treatment can be air.

[0077] The beta zeolite according to the present embodiment can be produced by the production method including the above-mentioned steps. The produced beta zeolite can be used as the propane selective adsorbent of the present embodiment. The produced beta zeolite may be mixed with other substances (binders, molding aids, and water) other than the beta zeolite as necessary, and the resulting mixture may be molded and fired to produce a propane selective adsorbent in the form of a molded body.

[0078] The propane selective adsorbent of the present embodiment described above is more likely to adsorb propane than propylene, and therefore can efficiently selectively adsorb propane from a mixed gas containing propane and propylene (propane-propylene mixed gas). Therefore, the propane selective adsorbent of the present embodiment can also be used in a purification method for selectively adsorbing propane from a propane-propylene mixed gas to purify propylene.

[0079] The selective adsorption of propane by the propane selective adsorbent of this embodiment can be carried out by contacting a propane-propylene mixed gas with the beta zeolite of this embodiment. The method of contacting the beta zeolite of this embodiment with the propane-propylene mixed gas is not particularly limited, but examples thereof include a method of filling the propane selective adsorbent of this embodiment into a fixed bed flow-type reaction tube and flowing the propane-propylene mixed gas therethrough, and a method of leaving the propane selective adsorbent of this embodiment in the propane-propylene mixed gas.

[0080] The propane-propylene mixed gas to be contacted with the beta zeolite according to the present embodiment may be composed of only propane and propylene, or may contain other components other than propane and propylene. Examples of other components other than propane and propylene include one or more selected from the group consisting of nitrogen, oxygen, helium, carbon dioxide, and argon.

[0081] In the propane-propylene mixed gas, the content ratio of propane and propylene is not particularly limited, and for example, the total of propane and propylene can be 10% by volume or more and 100% by volume or less with respect to 100% by volume of the mixed gas. The content ratio of propane and propylene in the propane-propylene mixed gas is also not particularly limited, and for example, the ratio of propylene in the propane-propylene mixed gas can be 4 parts by volume or more and 999 parts by volume or less with respect to 1 part by volume of propane. The propane selective adsorbent of this embodiment can be expected to selectively adsorb propane even in a propane-propylene mixed gas containing only a trace amount of propane, so the ratio of propylene in the propane-propylene mixed gas can be 19 parts by volume or more and 999 parts by volume or less with respect to 1 part by volume of propane.

[0082] The selective adsorption of propane by the propane selective adsorbent of this embodiment proceeds by contacting the beta zeolite of this embodiment with a propane-propylene mixed gas, so there is no particular limitation on the contact conditions between the beta zeolite and the mixed fluid. As an example, the contact temperature between the beta zeolite and the propane-propylene mixed gas can be 10°C or higher and 200°C or lower. In addition, the pressure of the atmosphere in which the beta zeolite and the propane-propylene mixed gas are contacted can be, for example, 0.01 MPa or higher and 1 MPa or lower. The contact time between the beta zeolite and the propane-propylene mixed gas can be appropriately set according to the amount of propane to be adsorbed.

[0083] The reason why the propane selective adsorbent of this embodiment can selectively adsorb propane is not clear, but it is believed that the SiO2 / Al2O3 molar ratio of the beta zeolite according to this embodiment is 1000 or more and Q 4 It is presumed that the (0Al) ratio of 98% or more allows the beta zeolite to interact more easily with propane than with propylene, and thus propane is more easily adsorbed than propylene. EXAMPLES

[0084] The present disclosure will be described in more detail below with reference to examples, but the present disclosure is not limited to these examples.

[0085] (Identification of crystalline phase) The samples were subjected to XRD measurement using a general powder X-ray diffractometer (name: Ultima IV Protectus, manufactured by Rigaku Corporation) under the following measurement conditions: Acceleration current / voltage: 40mA / 40kV Radiation source: CuKα radiation (λ=1.5405Å) Measurement mode: Continuous scan Scan condition: 40° / min Measurement range: 2θ=3° to 43° Divergence vertical limit slit: 10mm Divergence / entrance slit: 1° Receiving slit: open Detector: D / teX Ultra Ni filter used

[0086] The obtained XRD pattern was subjected to baseline correction and detection and intensity analysis of each XRD peak after correction using an analysis program (product name: IGOR Pro 8, manufactured by WaveMetrics) attached to the measuring device. The framework structure of the sample was identified by comparing the XRD pattern after correction with the XRD pattern (reference pattern) described in Zeolite Framework Types on the International Zeolite Society's website "http: / / www.iza-structure.org / databases / ". Note that the framework structure of layered silicates was identified by comparing with the XRD pattern described in a non-patent document (Chem. Commun., 2007, 5188-5190).

[0087] ( 29 Si DDMAS NMR measurement) A general solid-state nuclear magnetic resonance apparatus (apparatus name: AVANCE III 600, manufactured by Bruker) was used to measure the 29The Si DDMAS NMR spectrum was measured under the following conditions: 1 H resonance frequency: 600MHz 29 Si resonance frequency: 119.2MHz Rotor speed: 10kHz Repeat time: 30.0 seconds Accumulation count: 2048 times

[0088] Obtained 29 For Si DDMAS NMR spectra, peaks with peak tops between -120 ppm and -108 ppm were Q 4 (0Al)(Si(OSi)4)(Peak Q 4 (0Al) ) and the area of ​​the peak is S Q4(0Al) In addition, each peak with a peak top between -120 ppm and -90 ppm (peak Q All The sum of the areas of the above was taken as area S.

[0089] Peak fitting was performed using a standard NMR data processing software (software name: ALICE2, JEOL) by the least squares method using a mixture function of Gaussian distribution and Lorentzian distribution. Area integration was performed for each peak obtained by peak fitting, and the area S Q4(0Al) and area S were calculated. The calculated area S Q4(0Al) Substituting the area S into the above formula (1), Q 4 The (0Al) ratio was calculated. 4 If no peaks other than (0Al) are detected, Q 4 The (0Al) ratio was set to 100%.

[0090] (composition analysis) A sample solution was prepared by dissolving 2 mg of solid sample in 10 mL of acid solution (HF: 0.96 mass%, HNO3: 1.2 mass%) obtained by mixing hydrofluoric acid (HF concentration: 48 mass%), nitric acid (HNO3 concentration: 60 mass%), and pure water. The sample solution was measured by inductively coupled plasma atomic emission spectrometry (ICP-AES) using a general ICP device (device name: OPTIMA5300DV, manufactured by PerkinElmer). From the obtained measured values ​​of Si, Al, Na, K, and B, the converted values ​​were calculated as oxides (SiO2, Al2O3, Na2O, K2O, and B2O3), and the SiO2 / Al2O3 molar ratio, SiO2 / B2O3 molar ratio, Na2O content [ppm by mass], and K2O content [ppm by mass] of the solid sample were calculated from the calculated converted values.

[0091] (Measurement of BET specific surface area and pore volume) The amount of nitrogen gas adsorbed on the sample was measured using a general adsorption apparatus (apparatus name: BELSORP Max, manufactured by Microtrack-Bell). The BET value of the sample (BET specific surface area [m 2 The adsorption capacity (capacity) of the nitrogen gas was calculated by applying the t-plot method to the nitrogen gas adsorption isotherm. The t-plot method was performed using the analysis software (product name: BEL Master (version 7), manufactured by Microtrack-Bell) that came with the nitrogen adsorption apparatus. The nitrogen gas adsorption was performed using the usual constant volume method. The measurement conditions are as follows: Gas used: 99.999% nitrogen Measurement temperature: -196℃ Pretreatment: 400℃, reduced pressure heating (2 Pa or less) for 12 hours

[0092] (Propane adsorption evaluation) A general adsorption apparatus (apparatus name: BELSORP Max, manufactured by Microtrack-Bell) was used to measure the amount of propane gas adsorbed on the sample [mL(STP) / g]. A Langmuir plot was performed for the propane gas isotherm obtained by the measurement in the range of measurement pressures from 0.1 kPa to 40 kPa, and the adsorption equilibrium constant K1 [kPa -1 The adsorption amount Q1 [mol / kg] and the saturated adsorption amount Q1 [mol / kg] were obtained. From the obtained isotherm (approximate straight line), the change in the adsorption amount at a measurement pressure of 0.1 kPa to 10 kPa was calculated, and this change was taken as the effective propane adsorption amount [mL(STP) / g]. Note that a normal constant volume method was used for propane gas adsorption. The measurement conditions are as shown below, and the sample used was pretreated under the following conditions (pretreatment conditions). Gas used: 99.9% propane Measurement temperature: 25℃ Pretreatment: 400℃, reduced pressure heating (2 Pa or less) for 12 hours

[0093] (Propylene adsorption evaluation) The amount of propylene adsorbed on the sample [mL(STP) / g] was measured using a general adsorption apparatus (apparatus name: BELSORP Max, manufactured by Microtrack-Bell). A Langmuir plot was performed for the propylene gas isotherm obtained by the measurement in the range of measurement pressures from 0.1 kPa to 40 kPa, and the adsorption equilibrium constant K2 [kPa -1 The adsorption capacity Q2 [mol / kg] and the saturated adsorption amount Q2 [mol / kg] were calculated. The propylene gas adsorption was performed by a conventional constant volume method. The measurement conditions were as follows, and the samples used were pretreated under the following conditions (pretreatment conditions). Gas used: 99.95% propylene Measurement temperature: 25℃ Pretreatment: 400℃, reduced pressure heating (2 Pa or less) for 12 hours

[0094] Example 1 TEOS (purity 99% or more, manufactured by Kishida Chemical Co., Ltd.) and tetraethylammonium (hereinafter also referred to as "TEA") hydroxide 35 mass% aqueous solution (manufactured by Aldrich) were mixed and mixed for 90 minutes on a hot plate at 60°C. Next, pure water and hydrofluoric acid (HF concentration: 46 mass%, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were added and mixed well to obtain a raw material composition having the following molar composition. Al / Si ratio <0.001 (below detection limit) B / Si ratio <0.001 (below detection limit) TEA / Si ratio = 0.56 Na / Si ratio < 0.01 (below detection limit) K / Si ratio < 0.01 (below detection limit) H2O / Si ratio = 7.5 F / Si ratio = 0.56 OH / Si ratio < 0.01 (below detection limit)

[0095] The raw material composition was added with 0.01 times the mass of TEOS seed crystals (beta type zeolite, SiO2 / Al2O3 molar ratio: 115000), sealed in a PTFE inner cylinder stainless steel autoclave with an internal volume of 23 mL, and heat-treated at 150 ° C for 168 hours while rotating at 20 rpm. The product after the heat treatment was separated into solid and liquid, and washed with pure water of 50 times the mass of the obtained solid. The washed solid was dried in air at 80 ° C for 24 hours, and then calcined in air at 550 ° C for 6 hours to obtain zeolite, which was used as the adsorbent of this example.

[0096] The obtained zeolite had a SiO2 / Al2O3 molar ratio of 115,000, a Q4(0Al) ratio of 100%, a Na2O content of 8.0 mass ppm, a K2O content of 1.8 mass ppm, and a BET value of 559 m. 2 / g and pore volume of 0.22 cm 3The adsorbent (beta zeolite) had a molar ratio of SiO2 / Al2O3 of 100 / g (crystalline silicate (largest pore: 12-membered oxygen ring)). Figure 1 shows the NMR spectrum of the adsorbent (beta zeolite) of this example. Note that, while the Al / Si in the raw material composition could not be identified (it was below the detection limit), the SiO2 / Al2O3 molar ratio of the obtained beta zeolite was identified. This was thought to be because aluminum contained as an unavoidable impurity in the silica source (TEOS) and aluminum contained in the seed crystals became detectable by crystallization of the raw material composition (i.e., concentration of the raw material composition).

[0097] Example 2 A zeolite was obtained in the same manner as in Example 1, except that boric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was additionally mixed when mixing the 35 mass% aqueous solutions of TEOS and TEA hydroxides, and a raw material composition having the following molar composition was obtained, and this was used as the adsorbent of this example. Al / Si ratio <0.001 (below detection limit) B / Si ratio = 0.02 TEA / Si ratio = 0.56 Na / Si ratio < 0.01 (below detection limit) K / Si ratio < 0.01 (below detection limit) H2O / Si ratio = 7.5 F / Si ratio = 0.56 OH / Si ratio < 0.01 (below detection limit)

[0098] The obtained zeolite had a SiO2 / Al2O3 molar ratio of 24900, a SiO2 / B2O3 molar ratio of 140, a Q4(0Al) ratio of 100%, a Na2O content of 170 ppm by mass, a K2O content of 9.7 ppm by mass, and a BET value of 501 m. 2 / g, and a pore volume of 0.21 cm 3The obtained beta zeolite had a molar ratio of SiO2 / Al2O3 of 1.0 / g (crystalline borosilicate (largest pore: 12-membered oxygen ring)). Although the Al / Si ratio in the raw material composition could not be specified (it was below the detection limit), the SiO2 / Al2O3 molar ratio of the obtained beta zeolite was specified. This is considered to be because the aluminum contained as an unavoidable impurity in the silica source (TEOS) and the aluminum contained in the seed crystals became detectable by crystallization of the raw material composition (i.e., concentration of the raw material composition).

[0099] Comparative Example 1 A tetrapropylammonium (hereinafter also referred to as "TPA") hydroxide aqueous solution (manufactured by Aldrich, concentration: 1.03 mmol / g, K2O content: 3500 mass ppm) and fumed silica (manufactured by Cabot, Cab-O-Sil M5) were mixed, sealed in an airtight container with an internal volume of 23 mL, and stirred at 80°C for 2 hours to obtain a raw material composition having the following molar composition. Al / Si ratio <0.001 (below detection limit) B / Si ratio <0.001 (below detection limit) TPA / Si ratio = 0.24 Na / Si ratio < 0.01 (below detection limit) K / Si ratio = 0.02 H2O / Si ratio = 10.2 F / Si ratio < 0.01 (below detection limit) OH / Si ratio = 0.26

[0100] The raw material composition was sealed in a stainless steel autoclave with a PTFE inner cylinder having a capacity of 23 mL without adding seed crystals, and heat-treated at 135°C for 21 hours while rotating at 20 rpm. The product after the heat treatment was separated into solid and liquid, and washed with pure water in an amount 50 times the mass of the obtained solid. The washed solid was dried in air at 100°C for 24 hours, and then calcined in air at 600°C for 6 hours to obtain zeolite, which was used as the adsorbent of this comparative example.

[0101] The obtained zeolite had a SiO2 / Al2O3 molar ratio of 3340, a Q4(0Al) ratio of 97.7%, a Na2O content of 1100 mass ppm, a K2O content of 9670 mass ppm, and a BET value of 262 m. 2 / g and pore volume of 0.119 cm 3 The adsorbent (MFI zeolite) had a molar ratio of SiO2 / Al2O3 of 0.1 to 0.1 / g (crystalline silicate (largest pore: 10-membered oxygen ring)). Figure 1 shows the NMR spectrum of the adsorbent (MFI zeolite) of this comparative example. Note that, while the Al / Si in the raw material composition could not be identified (it was below the detection limit), the SiO2 / Al2O3 molar ratio of the obtained MFI zeolite could be identified. This was thought to be because aluminum contained as an unavoidable impurity in the silica source (fumed silica) became detectable by crystallization of the raw material composition (i.e., concentration of the raw material composition).

[0102] Comparative Example 2 A zeolite was obtained in the same manner as in Example 1, except that amorphous aluminum hydroxide (manufactured by Aldrich) was mixed with a 35% by mass aqueous solution of TEOS and TEA hydroxide to obtain a raw material composition having the following molar composition, and this was used as the adsorbent of this comparative example. Al / Si ratio = 0.0167 B / Si ratio <0.001 (below detection limit) TEA / Si ratio = 0.56 Na / Si ratio < 0.01 (below detection limit) K / Si ratio < 0.01 (below detection limit) H2O / Si ratio = 7.5 F / Si ratio = 0.56 OH / Si ratio < 0.01 (below detection limit)

[0103] The obtained zeolite had a SiO2 / Al2O3 molar ratio of 135, a Q4(0Al) ratio of 94.4%, a Na2O content of 83.3 mass ppm, a K2O content of 8.3 mass ppm, and a BET value of 526 m. 2 / g and pore volume of 0.21 cm 3The adsorbent was beta zeolite (crystalline aluminosilicate (largest pore: 12-membered oxygen ring)) with a molecular weight of 1.0 to 1.0 g. Fig. 1 shows the NMR spectrum of the adsorbent (beta zeolite) of this comparative example.

[0104] Comparative Example 3 Colloidal silica (product name: Ludox AS-40, manufactured by Aldrich), a 25 mass% aqueous solution of (1-adamantyl)trimethylammonium (hereinafter also referred to as "ATMA") hydroxide (manufactured by SACHEM), and a 46 mass% aqueous solution of hydrofluoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were mixed and stirred at 25°C for 24 hours to obtain a raw material composition having the following molar composition. Al / Si ratio <0.001 (below detection limit) B / Si ratio <0.001 (below detection limit) ATMA / Si ratio = 1.10 Na / Si ratio < 0.01 (below detection limit) K / Si ratio < 0.01 (below detection limit) H2O / Si ratio = 5.3 F / Si ratio = 1.10 OH / Si ratio < 0.01 (below detection limit)

[0105] The raw material composition was sealed in a stainless steel autoclave with a PTFE inner cylinder having an internal volume of 23 mL, and heat-treated at 175°C for 144 hours while rotating at 5 rpm. The product after the heat treatment was separated into solid and liquid, and washed with pure water in an amount 50 times the mass of the obtained solid. The washed solid was dried in air at 80°C for 24 hours, and then calcined in air at 600°C for 10 hours to obtain zeolite, which was used as the adsorbent of this comparative example.

[0106] The obtained zeolite had a SiO2 / Al2O3 molar ratio of 5570, a Q4(0Al) ratio of 91.0%, a Na2O content of 150 mass ppm, a K2O content of 8.6 mass ppm, and a BET value of 663 m. 2 / g and pore volume of 0.24 cm 3The obtained CHA-type zeolite had a molar ratio of SiO2 / Al2O3 of 1.0 / g (crystalline silicate (largest pore: oxygen 8-membered ring)). Although the Al / Si ratio in the raw material composition could not be specified (it was below the detection limit), the SiO2 / Al2O3 molar ratio of the obtained CHA-type zeolite was specified. This was thought to be because aluminum contained as an unavoidable impurity in the silica source (colloidal silica) became detectable by crystallization of the raw material composition (i.e., concentration of the raw material composition).

[0107] Comparative Example 4 TEOS (purity 99% or more, Kishida Chemical Co., Ltd.) and a 25% by mass aqueous solution of ATMA hydroxide (SACHEM Co., Ltd.) were mixed and mixed for 90 minutes on a hot plate at 60° C. Next, a 46% by mass aqueous solution of hydrofluoric acid (FUJIFILM Wako Pure Chemical Industries, Ltd.) was added and mixed to obtain a raw material composition having the following molar composition. Al / Si ratio <0.001 (below detection limit) B / Si ratio <0.001 (below detection limit) ATMA / Si ratio = 0.50 Na / Si ratio < 0.01 (below detection limit) K / Si ratio < 0.01 (below detection limit) H2O / Si ratio = 10 F / Si ratio = 0.50 OH / Si ratio < 0.01 (below detection limit)

[0108] The raw material composition was sealed in a stainless steel autoclave with a PTFE inner cylinder having an internal volume of 23 mL, and heat-treated at 150°C for 360 hours while rotating at 60 rpm. The product after the heat treatment was separated into solid and liquid, and washed with pure water in an amount 50 times the mass of the obtained solid. The washed solid was dried in air at 100°C for 24 hours, and then calcined in air at 600°C for 6 hours to obtain zeolite, which was used as the adsorbent of this comparative example.

[0109] The obtained zeolite was an STT-type zeolite (crystalline silicate (largest pore: oxygen 9-membered ring)) with a SiO2 / Al2O3 molar ratio of 40900, a Q4(0Al) ratio of 93.1%, a Na2O content of 18.4 mass ppm, and a K2O content of 8.2 mass ppm. Note that, while the Al / Si in the raw material composition could not be identified (it was below the detection limit), the SiO2 / Al2O3 molar ratio of the obtained STT-type zeolite could be identified. This was thought to be due to the fact that aluminum contained as an unavoidable impurity in the silica source (TEOS) became detectable by crystallization of the raw material composition (i.e., concentration of the raw material composition).

[0110] Comparative Example 5 A zeolite was obtained in the same manner as in Example 1, except that amorphous aluminum hydroxide (manufactured by Aldrich) was mixed with a 35% by mass aqueous solution of TEOS and TEA hydroxide to obtain a raw material composition having the following molar composition, and this was used as the adsorbent of this comparative example. Al / Si ratio = 0.002 B / Si ratio <0.001 (below detection limit) TEA / Si ratio = 0.56 Na / Si ratio < 0.01 (below detection limit) K / Si ratio < 0.01 (below detection limit) H2O / Si ratio = 7.5 F / Si ratio = 0.56 OH / Si ratio < 0.01 (below detection limit)

[0111] The obtained zeolite had a SiO2 / Al2O3 molar ratio of 940, a Q4(0Al) ratio of 100%, a Na2O content of 14 ppm by mass, a K2O content of 9 ppm by mass, and a BET value of 490 m 2 / g and pore volume of 0.20 cm 3 / g, it was a beta-type zeolite (crystalline aluminosilicate (largest pore: 12-membered oxygen ring)).

[0112] Comparative Example 6 Beta zeolite (product name: HSZ (registered trademark)-990HOA, manufactured by Tosoh Corporation) was used as the adsorbent in this comparative example. This zeolite has a SiO2 / Al2O3 molar ratio of 1700, a Q4 (0Al) ratio of 73.7%, a Na2O content of less than 1 ppm by mass (below the detection limit), a K2O content of 1 ppm by mass or less (below the detection limit), and a BET value of 462 m 2 / g and pore volume of 0.22 cm 3 / g, it was a beta-type zeolite (crystalline aluminosilicate (largest pore: 12-membered oxygen ring)).

[0113] Comparative Example 7 MFI type zeolite (product name: HSZ (registered trademark)-893HOA, manufactured by Tosoh Corporation) was used as the adsorbent in this comparative example. This zeolite was an MFI type zeolite (crystalline silicate (largest pore: 10-membered oxygen ring)) with a SiO2 / Al2O3 molar ratio of 2120, a Q4 (0Al) ratio of 99.0%, a Na2O content of 14.6 ppm by mass, and a K2O content of 1 ppm by mass or less (below the detection limit).

[0114] Comparative Example 8 Colloidal silica (product name: SH-3, manufactured by Fuso Chemical Co., Ltd.), a 25% by mass aqueous solution of ATMA hydroxide (manufactured by SACHEM), and a 48% aqueous solution of sodium hydroxide were mixed to obtain a raw material composition having the following molar composition. Al / Si ratio < 0.001 (below detection limit) B / Si ratio < 0.001 (below detection limit) ATMA / Si ratio = 0.20 Na / Si ratio = 0.20 K / Si ratio < 0.01 (below detection limit) H2O / Si ratio = 40 F / Si ratio < 0.01 (below detection limit) OH / Si ratio =0.40

[0115] The raw material composition was sealed in a stainless steel autoclave with an internal volume of 80 mL, and heat-treated at 170°C for 60 hours while rotating at 20 rpm. The product after the heat treatment was separated into solid and liquid, and washed with pure water in an amount 50 times the mass of the obtained solid. The washed solid was dried in air at 110°C for 24 hours, and then calcined at 750°C for 2 hours under a water vapor concentration of 20% by volume to obtain zeolite, which was used as the adsorbent of this comparative example.

[0116] The obtained zeolite had a SiO2 / Al2O3 molar ratio of 2250, a Q4(0Al) ratio of 97.8%, a Na2O content of 163000 mass ppm, a K2O content of 480 mass ppm, and a BET value of 232 m. 2 / g and pore volume of 0.08 cm 3 The AFI zeolite (crystalline silicate (largest pore: 12-membered oxygen ring)) had a molar ratio of SiO2 / Al2O3 of 100 / g. Note that, while the Al / Si in the raw material composition could not be specified (it was below the detection limit), the SiO2 / Al2O3 molar ratio of the obtained AFI zeolite was specified. This was thought to be because aluminum contained as an unavoidable impurity in the silica source (fumed silica) became detectable by crystallization of the raw material composition (i.e., concentration of the raw material composition).

[0117] Comparative Example 9 9.3 g of fumed silica (Cabot Corporation, Cab-O-Sil M5), 16.4 g of 26 mass% tetramethylammonium hydroxide aqueous solution, and 9.8 g of water were mixed and stirred for 1 hour. The obtained raw material composition was sealed in a PTFE inner cylinder stainless steel autoclave with an internal volume of 125 mL, and heat-treated at 170°C for 15 days under stationary conditions. The product after the heat treatment was separated into solid and liquid, and washed with pure water. The solid content after washing was dried in the air at 100°C for 12 hours. The obtained product was layered silicate PLS-1 (hereinafter also simply referred to as "PLS-1").

[0118] 0.50 g of the PLS-1 was mixed with 25.1 g of 0.3 mol / L hydrochloric acid and 0.17 g of dichlorodimethylsilane, and the resulting raw material composition was sealed in a 23 mL PTFE inner cylinder stainless steel autoclave and heat-treated at 170 ° C for 24 hours under stationary conditions. The product after heat treatment was separated into solid and liquid and washed with pure water. The washed solid was dried in the air at 80 ° C for 20 hours to obtain a product, which was used as the adsorbent of this comparative example.

[0119] The obtained product was layered silicate IEZ-1 (hereinafter also simply referred to as "IEZ-1"). The IEZ-1 had a SiO2 / Al2O3 molar ratio of 38700, a Q4(0Al) ratio of 85.1%, a Na2O content of 31.0 ppm by mass, and a K2O content of 47.1 ppm by mass.

[0120] Comparative Example 10 The IEZ-1 obtained in Comparative Example 9 was calcined in air at 500°C for 6 hours to obtain a calcined product, which was used as the adsorbent of this Comparative Example. The calcined product obtained was layered silicate IEZ-2 (hereinafter also simply referred to as "IEZ-2"). The IEZ-2 had a SiO2 / Al2O3 molar ratio of 38700, a Q4(0Al) ratio of 77.4%, a Na2O content of 31.0 mass ppm, and a K2O content of 47.1 mass ppm or less (below the detection limit).

[0121] Comparative Example 11 A metal-organic framework (manufactured by ACS Materials) having a ZIF-8 framework structure described in Non-Patent Document 2 was used as the adsorbent in this comparative example.

[0122] The results of propane / propylene adsorption evaluation of the adsorbents of the examples and comparative examples are shown in the table below. In Table 1 below, K1 / K2 is the value obtained by dividing the adsorption equilibrium constant K1 by the adsorption equilibrium constant K2. [Table 1] *In Comparative Example 11, since the Langmuir plot could not be applied in the measurement pressure range of 0.1 kPa or more and less than 15 kPa, the analysis was performed in the range of 15 kPa or more and 40 kPa or less.

[0123] From Table 1, it can be seen that the adsorbents of Examples 1 and 2 have a larger K1 / K2 than the adsorbents of Comparative Examples 1 to 3 and Comparative Examples 5 to 11. K1 / K2 is an index showing how easily propane is adsorbed relative to propylene, and K1 / K2 of 1.00 or more means that propane is more easily adsorbed than propylene, and the larger K1 / K2 is than 1.00 means that propane is more easily adsorbed than propylene. Therefore, it can be understood that Examples 1 to 2, which have a K1 / K2 of 1.00 or more and a larger K1 / K2 than Comparative Examples 1 to 3 and Comparative Examples 5 to 11, are more likely to adsorb propane than propylene compared to Comparative Examples 1 to 3 and Comparative Examples 5 to 11. It can also be understood that the adsorbents of Examples 1 to 2 have a larger effective propane adsorption amount than the adsorbents of Comparative Examples 1 to 3 and Comparative Examples 5 to 11.

Claims

1. The beta zeolite has a molar ratio of silica to alumina of 1000 or more, and the beta zeolite is 29 A propane selective adsorbent, in which the ratio of the total area of ​​peaks having peak tops in a chemical shift range of -120 ppm or more and -108 ppm or less to the total area of ​​peaks having peak tops in a chemical shift range of -120 ppm or more and -90 ppm or less in a spectrum measured by Si-DDMAS-NMR is 98% or more.

2. 2. The propane selective adsorbent according to claim 1, wherein the beta zeolite has an alkali metal content of 200 mass ppm or less calculated as an oxide.

3. The beta zeolite has an adsorption equilibrium constant K 2 Adsorption equilibrium constant K of propane on 1 2. The propane selective adsorbent of claim 1, wherein the ratio of

4. 2. The propane selective adsorbent according to claim 1, wherein the beta zeolite contains fluorine.

5. A method for selectively adsorbing propane, comprising contacting the beta zeolite contained in the propane selective adsorbent according to any one of claims 1 to 4 with a mixed gas containing propane and propylene.

6. A method for purifying propylene, comprising contacting the beta zeolite contained in the propane selective adsorbent according to any one of claims 1 to 4 with a mixed gas containing propane and propylene.